2009
DOI: 10.1016/j.jvs.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from cross-sectional imaging indicates abdominal but not thoracic aortic aneurysms are local manifestations of a systemic dilating diathesis

Abstract: A clear understanding of the pathophysiology of aortic aneurysms is essential. Observational studies have raised the suspicion that abdominal aortic aneurysms are a local representation of a systemic disease of the vasculature. Whether aneurysms of the thoracic aorta have a similar systemic tendency is unknown. Validation of this will open broader avenues of research clarifying understanding of the initiating factors of aneurysms and whether all aneurysms distributed through the arterial tree share the same et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…In this study, we highlight that AAA patients had a tendency toward increased 18F-FDG throughout nondilated sites of the aorta and carotid arteries compared with age-matched control subjects, implying that the entire vascular tree exhibits the enhanced glucose metabolism, and the aneurysmal formation assumes to be a focal manifestation of a systemic condition. 22,23 Further increased 18F-FDG uptake into the abdominal aneurysmal wall suggests enhanced glycolysis of constituent cell's capacity to incorporate glucose to meet energy demand. Aneurysmal process has been reported to extend into 1 or both common iliac arteries in 25% of the AAA cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we highlight that AAA patients had a tendency toward increased 18F-FDG throughout nondilated sites of the aorta and carotid arteries compared with age-matched control subjects, implying that the entire vascular tree exhibits the enhanced glucose metabolism, and the aneurysmal formation assumes to be a focal manifestation of a systemic condition. 22,23 Further increased 18F-FDG uptake into the abdominal aneurysmal wall suggests enhanced glycolysis of constituent cell's capacity to incorporate glucose to meet energy demand. Aneurysmal process has been reported to extend into 1 or both common iliac arteries in 25% of the AAA cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have provided evidence of an association between carotid artery lumen diameter and risk of aortic aneurysm formation in population-based samples (5–6). In the TromsĂž Study, investigators found that common carotid artery lumen diameter was independently associated with risk of abdominal aortic aneurysm in men (odds ratio, OR=1.9 [95% confidence interval, CI: 1.2–2.9]) and women (OR=4.1 [95% CI: 1.5–10.8]), suggesting an association between carotid artery dilatation and a general arterial dilating diathesis (5).…”
Section: Introductionmentioning
confidence: 99%
“…12 Patients with AAA exhibit arterial dilatation and altered matrix composition throughout the vasculature. 13,14 Elevation of MMP-2 occurs in arteries and veins remote from the aorta in patients with AAA, 15 and AAA are associated with generalized arteriomegaly, 16 carotid artery dilatation, 14 and coronary artery ectasia. 17 The inferior mesenteric vein (IMV) has been used as a tissue model of early aneurysmal changes previously.…”
mentioning
confidence: 99%